Leaching Process of Weathered Crust Elution-Deposited Rare Earth Ore With Formate Salts - Chen, Zhuo; Zhang, Zhenyue; Chi, Ruan (Frontiers in Chemistry, 2020)
To strengthen the rare earth leaching process and weaken the hydration of clay minerals for preventing the landslide, it is of great importance to adopt the green and sustainable leaching agent in the industry. In this work, the leaching process of weathered crust elution-deposited rare earth ores with formate salts (ammonium formate, potassium formate and sodium formate) was investigated. The effects of formate salts on the linear swelling ratio and zeta potential of the clay minerals were studied. The experimental results showed that ammonium formate could effectively recover the rare earth elements from weathered crust elution-deposited rare earth as well as inhibit the leaching of impurity aluminum. At room temperature, when the ammonium formate concentration was 1%wt, the leaching efficiencies of rare earth and aluminum were 87% and 37% respectively. Compared with traditional inorganic ammonium salts, the inhibition effect of impurity aluminum was obvious. In addition, the results of linear swelling ratio in the clay minerals showed that the inhibit ability of formate salts on the hydration of clay minerals enhanced with the increase of the formate concentration, and the order of the inhabitation on the clay minerals followed: 1% ammonium formate > 1.5% potassium formate > 2.5% sodium formate > distilled water. Based on the double layer theory, ammonium formate and potassium formate could effectively compress clay mineral particles to avoid the water entering, which can increased the interaction between clay mineral particles and greatly reduced the electronegative property of the clay minerals, so as to effectively reduce the surface hydration of clay mineral to decrease the swelling of rare earth ore. The results of this experiment have important and practical significance in guiding the prevention of landslide, promoting the in-situ leaching technology and effectively protecting the ecological environment in mining areas.